Assessment of DMFT Score in Lower Income Employees of the University of Faisalabad - Hina Barkaat, Tahmeena Atiq, Maleeha Khurram, Rida Ahmed, Sarosh Iqbal, Waqas Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Maintenance of oral health is directly linked to general well-being of an individual. Oral diseases are most common of public health problems because it effects human life due to lack of awareness, affordability and socio economic factors. Oral diseases can adversely affect the worker by compromising their performance and human well being. Material and Methods: Cross sectional research was done in The University of Faisalabad. The study participants included all the low income employees. All the employees of this category who were physically and mentally capable of responding to the questionnaire and provided informed consent were made part of the study. The 85 employees were selected and their DMFT score was assessed. SPSS version 23 was applied for data analysis. Results: P value was statistically significant in patient’s age group 1 (18-35 years) and group-2 (36-66) with oral Hygiene status and DMFT score. Conclusion: Based on existing data it was concluded that in older patients DMFT score was high and there oral hygiene was not being properly maintained. Keywords: Oral hygiene status, DMFT index, Socioecnomic status